Male Human Papillomavirus Vaccine Acceptance Is Enhanced by a Brief Intervention that Emphasizes Both Male-Specific Vaccine Benefits and Altruistic Motives. Issue 2 (February 2015) - Bonafide, Katherine E.; Vanable, Peter A.
Abstract : Background: Although female human papillomavirus (HPV) vaccine acceptance has been widely studied, research on vaccine uptake among boys and men is needed. Male HPV vaccination can provide both individual and community-level benefit by offering recipients personal health protection while concurrently minimizing HPV transmission and ultimately providing female health protection. As such, male vaccine acceptance may be enhanced by emphasizing both altruistic motives (female health protection) and personal health benefits. Methods: A university-based sample of young men completed computer-administered surveys and viewed informational interventions that varied in the inclusion or exclusion of altruistic motives and in the level of emphasis on male-specific HPV-related illnesses and vaccine benefits. Human papillomavirus vaccine acceptance was assessed immediately after intervention. Results: Participants who received the intervention emphasizing both altruistic motives and male-specific information endorsed the greatest vaccine acceptance (mean [SD], 3.6 [1.0]). Conclusion: Provider and community-level interventions highlighting both altruistic motives and personal health vaccine benefits may enhance HPV vaccine uptake among young men. Abstract : Findings from a brief informational intervention study supported predictions that presenting men with both male-specific human papillomavirus vaccine information and altruistic motives for vaccination enhances male interest in receiving the human papillomavirus vaccine.